Performance of horizontal drains in residual soil slopes - Rahardjo, Harianto (2011)
In tropical and subtropical regions, shallow landslides often occur in residual soil slopes. Short duration and high intensity rainfall will increase pore-water pressure and as a result, shear strength of soil in slopes decrease and stability of the slopes is affected. In this study, horizontal drains were installed in a residual soil slope in Singapore in order to improve stability of the slope. The slope was instrumented with tensiometers and piezometers in order to investigate the effectiveness of horizontal drains as a slope stabilization method against rainfall-induced slope failures. Variation of water table elevation and matric suction in the slope due to rainfall events was monitored. In addition, numerical analyses of seepage in the slope due to rainfall were carried out and the results show reasonably good agreement with the monitoring data from field measurements. Field monitoring results indicate that horizontal drains are effective in lowering water table and increasing stability of the investigated slope. Therefore, horizontal drains are considered to be a useful and economical method for improving the stability of residual soil slopes against rainfall.